KINERJA KEUANGAN PADA KABUPATEN KAPUAS PROVINSI KALIMANTAN TENGAH - Ni Putu Agustinawati; Maria Yanida (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Aim of this study is to analyze the performance of finance in Kapuas Local Government in regional financial management according to APBD (Local Government Budget) 2020, reviewed by financial ratio analysis encompassing local financial independence ratio, effectivity ratio, and growth ratio with its realization. Data which are used to analyze the aforementioned ratios are derived from Kapuas Local Government’s budget realization report year 2019 and 2020. Results of the study indicate the financial independence of Kapuas Regency had reached 5.49% in 2020 and 6.03% in 2021, from which it can be reckoned that Kapuas Local Government has successfully raised its financial independence ratio. Effectivity ratio of Kapuas Local Government is shown to attain 92.62% in 2020, which is considered to be effective, and increase to 94.38% in 2021 from which Kapuas Local Government’s effectivity ratio is considered to be preferable than prior year. PAD (Local Own-source Revenue) growth in 2020 decreased in insignificant amount from prior year, while in 2021 Kapuas Local Government has attained 9.18% of PAD growth that conveys Kapuas Local Government in 2021 has attained advanced performance than 2020.